Burden of diabetic macular oedema in patients receiving antivascular endothelial growth factor therapy in South Korea: a healthcare resource use and cost analysis. Issue 12 (29th December 2020) - Jeon, Ha-Lim; Lee, Hyesung; Yoon, Dongwon; Lee, Yeonkyung; Kim, Jae Hui; Jee, Donghyun; Shin, Ju-Young
Abstract : Objective: To examine healthcare resource utilisation (HRU) and direct medical costs for patients with diabetic macular oedema (DME) treated with antivascular endothelial growth factor (anti-VEGF) in Korea by comparing with those for (1) patients with diabetes mellitus (DM) without retinopathy and (2) patients with neovascular age-related macular degeneration (nAMD) treated with anti-VEGF. Design: Retrospective cohort study. Setting: The Korean National Health Insurance (NHI) database from 1 January 2014 to 31 December 2016. Participants: We identified 1398 patients older than 30 years of age who received anti-VEGF treatment for DME in 2015 after excluding patients who had a diagnosis of nAMD in 2015 and any cancer in the preceding year. Main outcome measures: One-year healthcare resource use and direct medical costs of patients with DME treated with anti-VEGF. Results: In total, 1398 patients with DME receiving anti-VEGF, 12 813 patients with DM without retinopathy and 12 222 patients with nAMD receiving anti-VEGF were identified. Hospital admissions and outpatient visits were highest in patients with DME, while the number of licensed anti-VEGF injections in those with DME was about half that of those with nAMD (2.1 vs 3.9 per patient per year). Mean 1-year medical costs were also higher in patients with DME (US6723) than in those with DM without retinopathy (US2687) and nAMD (US4980). In a multivariable analysis with matched cohorts, DME was associated with 66% higher medical costs for comorbid diseases (adjusted OR (aOR), 1.66; 95% CI 1.45 to 1.90) and 50% lower anti-VEGF injections (aOR, 0.50; 95% CI 0.46 to 0.54) compared with nAMD. Conclusions: The overall HRU and economic burden for DME treated with anti-VEGF were higher than for DM without retinopathy or for nAMD treated with anti-VEGF. Meanwhile, the lower number of licensed anti-VEGF injections compared with nAMD may reflect a potential lack of ophthalmological treatment for DME supported by the NHI in Korea.